Pengaruh Kepemimpinan Transformasional, Sistem Pengendalian Manajemen, dan Karakteristik Sistem Informasi Akuntansi Manajemen terhadap Kinerja Manajerial Pada Perusahaan Manufaktur Kabupaten Tangerang - Meliani, Kharisma Ayu; Bastian, Elvin (Innovative: Journal Of Social Science Research, 2024)
The goal of this study is to examine how managerial performance can be affected by transformational leadership, management control systems, and characteristics of management accounting information systems. This study is a kind of quantitative research where information from respondents, namely middle managers employed by industrial companies in Tangerang Regency and collected through the use of primary data in the form of questionnaires. The quantitative descriptive analysis method is the analysis technique used in this study and uses IBM SPSS Version 25 as the analysis tool used. The findings of the study are as follows: 1) Managerial performance is positively and significantly influenced by transformational leadership. 2) Managerial performance is positively and significantly influenced by the management control system. 3) Managerial performance is positively and significantly influenced by the characteristics of management accounting information systems.